2014
DOI: 10.1371/journal.pone.0105962
|View full text |Cite
|
Sign up to set email alerts
|

Might Cortical Hyper-Responsiveness in Aging Contribute to Alzheimer’s Disease?

Abstract: Our goal is to understand the neural basis of functional impairment in aging and Alzheimer’s disease (AD) to be able to characterize clinically significant decline and assess therapeutic efficacy. We used frequency-tagged ERPs to word and motion stimuli to study the effects of stimulus conditions and selective attention. ERPs to word or motion increase when a task-irrelevant 2nd stimulus is added, but decrease when the task is moved to that 2nd stimulus. Spectral analyses show task effects on response power wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Database searches were conducted in PsycINFO and PubMed for peer-reviewed articles in the English language. MCI searches using the keywords ["ERP" OR "event-related potential"] combined with ["MCI" OR "mild cognitive impairment"] returned a combined 169 results (69 PsycINFO; 100 PubMed). To assure comprehensive coverage, all 42 studies from Gu and Zhang's review [58] were added to the initial return list, resulting in a complete initial list of 211 studies.…”
Section: Search Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Database searches were conducted in PsycINFO and PubMed for peer-reviewed articles in the English language. MCI searches using the keywords ["ERP" OR "event-related potential"] combined with ["MCI" OR "mild cognitive impairment"] returned a combined 169 results (69 PsycINFO; 100 PubMed). To assure comprehensive coverage, all 42 studies from Gu and Zhang's review [58] were added to the initial return list, resulting in a complete initial list of 211 studies.…”
Section: Search Strategiesmentioning
confidence: 99%
“…The majority of the 25 studies that analyzed P300 amplitude reported smaller amplitude in AD compared to HC groups [i.e., 60%; 3,4,13,42- 43,60,63,71,84,89,114,118,142,145,152], including one reporting a trend that did not reach statistical significance[42]. The remaining ten studies reported no significant difference between groups [i.e., 40%;31,47,69,[72][73]92,105,110,126,139]. These latter AD studies were notable for small sample sizes (e.g., eight per cell), age differences between groups, high AD group MMSE scores (e.g., 27/30), and/or simple tasks (i.e., 67% oddball paradigms), which may have limited power to detect group differences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This mirrors prior findings of exaggerated alpha-gamma synchronization between nodes of the default mode network in older adults during the resting-state, associated with impaired working memory performance and interpreted as being “stuck” in default mode (Pinal et al, 2015). Enhanced synchronization and cross-parameter coupling could reflect compensatory mechanisms to sustain neural dynamics in the face of reduced signal power or complexity (Ansado et al, 2012; Jacob & Duffy, 2014; Meunier et al, 2014; Morcom & Henson, 2018; Zahodne & Reuter-Lorenz, 2019). Longitudinal studies are needed to determine whether increased synchronization precedes the loss of complexity or results from a compensatory process.…”
Section: Discussionmentioning
confidence: 99%